Club Theory and Household Formation - Hans Gersbach; Hans Haller (ETH Zurich, CER-ETH - Center of Economic Research, 2009)
The relationship between our general equilibrium model with multi- member households and club models with multiple private goods is investigated. The main distinction in the definitions consists of the equilibrium concepts. As a rule, competitive equilibria among house- holds where no group of consumers can benefit from forming a new household and valuation equilibria prove equivalent in the absence of consumption externalities, but not in their presence.
Keywords: D13; D50; D62; D71; 330; Household Behavior; Household Formation; General Equilibrium; Clubs; Haushaltsökonomik; Clubtheorie; Allgemeines Gleichgewicht; Theorie